ESTUDO DE CASO DE UMA PACIENTE COM DIAGNÓSTICO DE ACIDENTE VASCULAR ENCEFÁLICO - Loro, Marli M.; Kolankiewicz, Adriane C. B.; Mertins, Simone M.; Golle, Lidiane; Rorato, Luciéle; Dallabrida, Francieli A. (Salão do Conhecimento, 2013)
Resumo